2000
DOI: 10.1099/0022-1317-49-1-63
|View full text |Cite
|
Sign up to set email alerts
|

Identification of mutans and other oral streptococci by random amplified polymorphic DNA analysis

Abstract: The identification and classification of the non-haemolytic or viridans group of streptococci have long been recognised as difficult and unsatisfactory. Phenotypic and genotypic heterogeneity have resulted in ambiguous speciation, particularly with mutans streptococci and other oral streptococci. This study was done to determine whether random amplified polymorphic DNA (RAPD) analysis is useful to identify and even classify oral and other streptococci. DNA was prepared and purified from 25 strains of mutans st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Additional studies are using plasmid analysis to investigate the transfer of antibiotic resistance genes in order to link RAPD fingerprints to antibiotic resistance and sensitivity. This investigation supports previous reports that RAPD analysis is efficient, reproducible, and capable of detecting genomic polymorphisms among various microbial species without previous knowledge of the nucleotide sequence on the target DNA (22), and the technique has been shown to be valuable in studies dealing with biofilm (22,25). RAPD is also preferable for gram-positive species, where chromosomal preparations are difficult and low concentrations of nucleic acid are achieved.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Additional studies are using plasmid analysis to investigate the transfer of antibiotic resistance genes in order to link RAPD fingerprints to antibiotic resistance and sensitivity. This investigation supports previous reports that RAPD analysis is efficient, reproducible, and capable of detecting genomic polymorphisms among various microbial species without previous knowledge of the nucleotide sequence on the target DNA (22), and the technique has been shown to be valuable in studies dealing with biofilm (22,25). RAPD is also preferable for gram-positive species, where chromosomal preparations are difficult and low concentrations of nucleic acid are achieved.…”
Section: Discussionsupporting
confidence: 76%
“…The B. brevis isolates were purified from two specific locations on the same tube from one patient, the inner portion of the internal stabilizer and the outer portion of the shaft. A hypothesis, supported by several reports (1,22), can be drawn that the isolates came from different environmental sources and were not from one organism proliferating through various locations of the tube. B. licheniformis was found in biofilms isolated from three different patients, and all of the RAPD profiles were different, leading to the hypothesis that each patient encountered different environmental sources of the contaminant that produced biofilm proliferation.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, Truong et al (38) analyzed reference strains of oral streptococci using RAPD for the identification and subclassification of all the studied strains and suggested that RAPD can be valuable to discriminate the species S. mutans and S. sobrinus, both from each other and from other oral streptococci. However, similarly to those authors, the present study indicated that the RAPD markers discriminated the strains ATCC 13540 and BAA572 of S. pyogenes, forming a separate group (Group II, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several markers based on the PCR method have been utilized to identify bioserotypes of the mutans group and their relative occurrence within the oral microbiota (14,16,21,25,31,32). Among those, RAPD markers have been widely used in the study of the genetic polymorphism and in the distribution of populations of S. mutans (13,18,19,29,34,38).…”
Section: Introductionmentioning
confidence: 99%
“…eDNA was isolated from the biofilm by the same procedure as in the quantification of eDNA. RAPD was carried out using the random primers that were published previously: OPA02 (5=-TGCCGAGCTG-3=) and OPA18 (5=-AGGTGACCGT-3=) (49,50). The PCR was conducted using the PrimeSTAR premix (TaKaRa Bio, Inc., Shiga, Japan) under the following cycling conditions: 94°C for 1 min, 32°C for 1 min, and 72°C for 2 min for 40 cycles.…”
Section: Methodsmentioning
confidence: 99%